PENERAPAN GAME EDUKASI BINGO PADA MATERI OPERASI HITUNG BILANGAN CACAH UNTUK MENINGKATKAN KOGNITIF SISWA KELAS IV SDN DAYAH TANOH - Junaidah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2026)
This study aims to determine the application of the Bingo Educational Game-based method on the Arithmetic Operations of Whole Numbers concept to improve the cognitive abilities of 4th grade students of SDN Dayah Tanoh. The research design used is Classroom Action Research (CAR) with the Kemmis and Mc. Taggart research design. The subjects in this study were 21 4th grade students. Data collection techniques in the study were carried out through observation, tests, and documentation. The results showed that the average value in cycle I was 48.80 with a completion percentage of 9.53%, in cycle II with an average value of 75.23 with a completion percentage of 57.14%, then in cycle III increased again with an average value of 85.52 with a completion percentage of 85.71. From these results, it can be concluded that the application of the Bingo Educational Game-based method can improve the cognitive abilities of 4th grade students of SDN Dayah Tanoh